New progress in roles of TGF-β signaling crosstalks in cellular functions, immunity and diseases - Shuchen Gu; Rik Derynck; Ye-Guang Chen; Xin-Hua Feng (Cell Regeneration, 2024)
Abstract The family of secreted dimeric proteins known as the Transforming Growth Factor-β (TGF-β) family plays a critical role in facilitating intercellular communication within multicellular animals. A recent symposium on TGF-β Biology - Signaling, Development, and Diseases, held on December 19–21, 2023, in Hangzhou, China, showcased some latest advances in our understanding TGF-β biology and also served as an important forum for scientific collaboration and exchange of ideas. More than twenty presentations and discussions at the symposium delved into the intricate mechanisms of TGF-β superfamily signaling pathways, their roles in normal development and immunity, and the pathological conditions associated with pathway dysregulation.